2018
DOI: 10.1016/j.jses.2017.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional kinematic analysis of throwing motion focusing on pelvic rotation at stride foot contact

Abstract: BackgroundBecause the throwing motion can be considered a kinetic chain, pelvic and trunk motion should be included in the analysis. Early pelvic rotation during the throwing sequence has been reported to be a factor leading to overloading of the shoulder and the elbow. A large pelvic rotation angle at the stride foot contact (SFC) was thought to indicate early pelvic opening. This study examined the kinematic features in each motion segment associated with increased pelvic rotation at SFC in pitchers of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…A set of 24 retroreflective markers were attached to the participant. 15,39 Markers were placed bilaterally on the acromion process, elbow epicondyles (lateral and medial), styloid processes (ulnar and radial), greater trochanter, femoral epicondyles (lateral and medial), malleoli (lateral and medial), and third distal metatarsal. Additionally, a marker was placed between the second and third distal metacarpals on the throwing hand and another on the heel of the left foot.…”
Section: Methodsmentioning
confidence: 99%
“…A set of 24 retroreflective markers were attached to the participant. 15,39 Markers were placed bilaterally on the acromion process, elbow epicondyles (lateral and medial), styloid processes (ulnar and radial), greater trochanter, femoral epicondyles (lateral and medial), malleoli (lateral and medial), and third distal metatarsal. Additionally, a marker was placed between the second and third distal metacarpals on the throwing hand and another on the heel of the left foot.…”
Section: Methodsmentioning
confidence: 99%
“…Overhand pitching is a movement that requires the coordination of the lower extremity, trunk, and upper extremity segments to effectively transfer force throughout the kinetic chain to project a baseball. It has been reported that angular velocities at the shoulder joint during overhand pitching can reach magnitudes near 7000°/s at the point of ball release [5].…”
Section: Introductionmentioning
confidence: 99%
“… 22 , 23 ) Moreover, Oi et al demonstrated that early pelvic rotation was correlated with decreased hip flexion of the stance leg and increased hip flexion of the lead leg from the cocking phase to the acceleration phase in young baseball players. 24 ) These results suggested that decreased hip IR ROM of the stance leg at 90° of flexion could lead to insufficient trunk rotation and breakdown of the kinetic chain of the throwing cycle, which could result in elbow and shoulder pain. In our study, negative correlations were found between age and hip ROMs of the stance leg measured in the prone position.…”
Section: Discussionmentioning
confidence: 95%